Potentially harmful excipients in neonatal medications: a multicenter nationwide observational study in Japan - Jumpei Saito; Naomi Nadatani; Makoto Setoguchi; Masahiko Nakao; Hitomi Kimura; Mayuri Sameshima; Keiko Kobayashi; Hiroaki Matsumoto; Naoki Yoshikawa; Toshihiro Yokoyama; Hitomi Takahashi; Mei Suenaga; et al. (BMC, 2021)
Abstract Background A multicenter investigation of neonate exposure to potentially harmful excipients (PHEs) in neonatal intensive care units (NICUs) in Japan has not been conducted. Methods A multicenter nationwide observational study was conducted. Neonate patient demographic data and information on all medicines prescribed and administered during hospitalization on 1 day between November 2019 and March 2021 were extracted from the medical records. Nine PHEs, paraben, polysorbate 80, propylene glycol, benzoates, saccharin sodium, sorbitol, ethanol, benzalkonium chloride, and aspartame, were selected. PHEs were identified from the package insert and the Interview Form. The quantitative daily exposure was calculated if quantitative data were available for each product containing the PHE. Results Prescription data was collected from 22 NICUs in Japan. In total, 343 neonates received 2360 prescriptions for 426 products containing 228 active pharmaceutical ingredients. PHEs were found in 52 (12.2%) products in 646 (27.4%) prescriptions for 282 (82.2%) neonates. Benzyl alcohol, sodium benzoates, and parabens were the most common PHEs in parenteral, enteral, and topical formulations, respectively. Quantitative analysis showed that 10 (10%), 38 (42.2%), 37 (94.9%), and 9 (39.1%) neonates received doses exceeding the acceptable daily intake of benzyl alcohol, polysorbate 80, propylene glycol, and sorbitol, respectively. However, due to the lack of quantitative information for all enteral and topical products, accurate daily PHE exposure could not be quantified. Conclusions Neonates admitted to NICUs in Japan were exposed to PHEs, and several of the most commonly prescribed medicines in daily clinical practice in NICUs contained PHEs. Neonate PHE exposure could be reduced by replacing these medicines with available PHE-free alternatives.